The meaning of violence or the meaningless violence: adolescents' view on the media - Kathie Njaine; Mariana Barcinski (Faculdade de Medicina de Botucatu (Unesp), 2007)
The present article is based on a qualitative study that aims to investigate the meanings attributed by adolescents to the violence in the media, especially on television, and the ways in which this group interacts with this media and appropriates its messages. The goal is to understand how the phenomenon of violence, mediated by television, is interpreted, incorporated or disapproved by adolescents in their everyday lives. Four focus groups with students from the seventh and eighth grades in São Gonçalo were conducted, in two public schools (one state and one municipal) and two private schools (one of middle-class and one of lower-class students), totalizing 33 adolescents. It was concluded that one of the challenges for the field of public health is to improve its performance in the prevention of violence, taking into account the relevance of the media in constructing a discourse on violence. We call attention for the urgent need to understand the dimension and the psychological and cultural impact of violence in the media on Brazilian children and adolescents, once this phenomenon has been creating feeling of fear, anguish, and the seek for security. The positive aspect of the media as a potential partner in the education and promotion of children and adolescents' health is pointed out. The denaturalization of some notions of violence given by the media, and the construction of spaces in the media for the youngsters to express themselves are some ways for health promotion and violence prevention.